1998
DOI: 10.1007/s001340050665
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of air tonometry with gastric tonometry using saline and other equilibrating fluids: an in vivo and in vitro study

Abstract: There are clinically significant differences in values for gastric mucosal PCO2 measured by air tonometry and saline tonometry both in vivo and in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…While air tonometry has simplified the measurement process (over saline tonometry) and eliminated the possible errors associated with the use of non-buffered saline this technology has a number of limitations [44][45][46]85,86]. Gastric tonometry is logistically and practically difficult and this may be the main factor that has prevented the widespread use of this technology.…”
Section: Sublingual Capnometrymentioning
confidence: 97%
See 1 more Smart Citation
“…While air tonometry has simplified the measurement process (over saline tonometry) and eliminated the possible errors associated with the use of non-buffered saline this technology has a number of limitations [44][45][46]85,86]. Gastric tonometry is logistically and practically difficult and this may be the main factor that has prevented the widespread use of this technology.…”
Section: Sublingual Capnometrymentioning
confidence: 97%
“…Air tonometry, particularly in conjunction with an automated system has a number of advantages when compared with conventional saline tonometry. Unlike saline tonometry, in-vitro studies have demonstrated that air tonometry has a very low bias with excellent precision [44][45][46]. Furthermore, automated air tonometry has an equilibration time of less than 20 minutes and being fully automated may eliminate potential sources of error associated with saline tonometry.…”
Section: Gastric Tonometrymentioning
confidence: 98%
“…It has been recognized, however, that saline may yield erroneous PCO 2 values, and that the bias may depend on the solution and the type of blood gas machine used to measure PCO 2 [1,3,4,5]. Indeed, the bias may be buffer- and pH-dependent [1,3,5].…”
Section: Full Textmentioning
confidence: 99%
“…Some of these problems may be avoided with air tonometry, in which surrounding intraluminal gastric carbon dioxide is allowed to rapidly equilibrate with the air-filled tonometer balloon PCO 2 [4,6]. Various types have been proposed, depending on the mode of recirculation of air in the catheter between measurement intervals, and one is commercially available (Tonocap; Datex, Helsinki, Finland) [1,5,6].…”
Section: Full Textmentioning
confidence: 99%
“…However, the tonometric measurements of Pi CO 2 needed to calculate these parameters may be influenced by various factors, including temperature [1,2].…”
mentioning
confidence: 99%